SISTEM INFORMASI PEMBAGIAN KELAS SISWA BARU MENGGUNAKAN METODE K-MEANS CLUSTERING PADA SMPN 9 PALANGKA RAYA BERBASIS WEBSITE - Oktaviyani, Enny Dwi; Karolita, Devi; Licantik, Licantik; Pransika, Yuni (Universitas Palangka Raya, 2018)
The information system of classroom division is a process done by Junior HighSchool 9 Palangka Raya to divide the students into several classes. In this process schoolsare still using manual methods. To support the system in the division of the classes to bebetter, then the information system of classroom division using k-means clusteringmethod by website based on Junior High School 9 Palangka Raya was made.This classroom divide information system uses the waterfall method. In this methodseveral steps to build software, namely: Requirements Definition, System and SoftwareDesign, Implementation and Unit Testing, Integration and System Testing and Operationand Maintenance. Creating a Data Flow Diagram (DFD). Entity Relationship Diagram(ERD), database design using PhpMyAdmin, User Interface design using Cascading StyleSheet, Dreamweaver and other tools to create reports.This classroom division information testing system uses Blackbox Testing thatfocuses on functional requirements in software based on the software requirementsspecification. Management of the system that is in the form of added data, change thedata, delete data and print data applied so that users can be active in this system.